Diagnosis, management, and pathophysiology of post-Fontan hypoxaemia secondary to Glenn shunt related pulmonary arteriovenous malformation. Issue 4 (1st October 1999) - Premsekar, R; Monro, J L; Salmon, A P
Abstract : An 8 year old child with tricuspid atresia had developed right sided pulmonary arteriovenous malformations following a previous classic Glenn procedure. These became clinically manifest immediately after Fontan conversion because of severe systemic desaturation. The pathophysiology and postoperative medical management of this case is described and related to current understanding of the aetiology of acquired pulmonary arteriovenous malformations following cavopulmonary shunt.